The relationship between shoulder pain and scapular mobility in teenage baseball players - Chen, C. -N.; Cheng, S. C.; Chang, B. -F.; Chang, H. -Y. (ISBS - Conference Proceedings Archive (Konstanz), 2012)
The purpose of this study was to identify the relationship between shoulder pain and scapular mobility for teenage baseball players. Thirty-five teenage baseball players (shoulder pain, n=11; healthy, n=24) were recruited in this study. The lateral scapula slide test (LSST), which represented as scapular mobility, was used to measure the scapular position and symmetry under varying loads. The result of this study showed that there was a difference in distance from the superior angle of the scapula to the spinous process of T2 between the two groups at shoulder 90 degree abduction.